Mineral and structural features of jewelery wood tin - D. A. Petrochenkov (Известия высших учебных заведений: Геология и разведка, 2017)
A mineral composition and gemological descriptions of the jewelery varieties of the wood tin of deposits Dzhalindinskoe (Khabarovskiy krai), Tynooken (East Chukotka) and Dominion Krik (Canada) have been explored. According to the data of radio-graphical analysis, wood tin consists mainly of cassiterite (76-98 mas.%). As admixtures, quartz, microcline and roentgenoamorphous phase have been found. Microinclusions of dzhalindite, preisingerite, acanthite, native bismuth, monazite and hemiatite have been found in wood tin by electronic-probe investigations. Color zonality of wood tin is defined by mineral composition, concentration of elements-admixtures (Fe, As) and microinclusions of hematite in cassiterite. Jewelery varieties of the wood tin are mainly connected with rhyolite , rarely with silicate and sulphide industrial types of tin deposits.